54.1: Invited Paper: Perovskite Light Emitting Diode. (24th February 2021) - Li, Danyang; Mu, Lan; Yip, Hin-Lap; Peng, Junbiao
Abstract : Metal halide perovskite materials occupy an increasingly important position in the field of optoelectronic materials due to their excellent light absorption properties, long carrier dispersion length and high mobility. However, the instability of perovskite materials is still a major factor constraining its development. So, its' important to improve the stability of perovskite materials in air and even to produce high‐performance LEDs in air. Here, we proposed a simple way to improve the stability of perovskite quantum dots and achieved the preparation of perovskite light‐emitting diodes in air. And green PQDs‐LED devices are fabricated by inkjet printing.